2020
DOI: 10.7146/lt.v5i7.120865
|View full text |Cite
|
Sign up to set email alerts
|

Elevernes trivsel og mentale sundhed

Abstract: På basis af et survey for elever og forældre vedrørende nødundervisningen under coronakrisen sætter denne artikel fokus på, hvordan coronakrisen påvirkede elevernes trivsel og mentale sundhed, hvilke bekymringer de selv og forældrene havde, og hvordan begge parter håndterede skolelukningerne. Næsten alle børnene savnede vennerne, skolen og fritiden, og knap en femtedel følte sig ensomme. Dels blev den fysiske kontakt med vennerne stærkt reduceret, dels var mange af børnene usikre på deres egen læring, hv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…In addition to the impact of an increased expectation of performance and competition, and an unpredictable labor market, increased individualization and self-representation in real life and on social media [4][5][6], the prolonged and devastating COVID-19 pandemic has prompted a global call to address the impact on the well-being of children and young people [7], but lack of knowledge about the long-term impact resulting from the many, mutually interacting, factors, makes it difficult to act on this call. Multiple studies conducted across various countries have reported a decline in students' well-being during the pandemic [8][9][10][11][12][13]. Some of these studies have also identified variations regarding age and gender [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the impact of an increased expectation of performance and competition, and an unpredictable labor market, increased individualization and self-representation in real life and on social media [4][5][6], the prolonged and devastating COVID-19 pandemic has prompted a global call to address the impact on the well-being of children and young people [7], but lack of knowledge about the long-term impact resulting from the many, mutually interacting, factors, makes it difficult to act on this call. Multiple studies conducted across various countries have reported a decline in students' well-being during the pandemic [8][9][10][11][12][13]. Some of these studies have also identified variations regarding age and gender [12,13].…”
Section: Introductionmentioning
confidence: 99%